Metoda promocji jako typ metody regulacji - Małecki, Witold (Wydawnictwo Uniwersytetu Wrocławskiego, 2017)
Method of promotion forms apart of the dispositive method of regulation (in abroad sense) which is typical for the method of regulation in the field of economic law. Method of promotion is marked by the benefits that are provided for entrepreneurs who follow patterns of behavior indicated in non-binding promotional norms. The benefits may be of financial nature, consisting of state aid measures and tax exemptions. In the Polish legislation the method of promotion is used to encourage entrepreneurs to conduct innovative activities, employ people with disabilities and participate in the social integration of excluded people.
Keywords: metody regulacji; promocja; ekonomia